Analysis Of Oxygen Sensor Dynamics For Catalytic Converter Diagnostics Using On-Board Logging Data - Klimov, Serhii; Khitrov, Igor (Моделювання, керування та інформаційні технології, 2025)
A catalytic converter is an important component of modern internal combustion engines, used to reduce the toxicity of exhaust gases by neutralizing harmful components such as nitrogen oxides, carbon monoxide, and unburned hydrocarbons. Successful operation of the converter requires maintaining a stoichiometric ratio of fuel to oxygen, which for gasoline engines is 14.7:1. This ratio is controlled by an automatic control system, the key element of which is an oxygen sensor (lambda probe). This paper aims to experimentally study the efficiency of a three-way catalytic converters (TWC) by analyzing the dynamics of oxygen sensor signals obtained using an on-board diagnostic system (OBD). The diagnostic method is based on comparing ECU signals from sensors before (Sensor 1) and after (Sensor 2) the catalytic converter. Real data from OBD parameter logging (Engine Load, RPM, O2 Sensor Voltages) during movement was used for analysis. Data analysis showed that under conditions of dynamic movement and load changes (Engine Load), the control sensor signal (Sensor 1) fluctuated constantly (0.1–0.9 V), while the diagnostic sensor signal (Sensor 2) remained consistently high (0.6–0.7 V). This behavior confirms that the TWC successfully accumulates oxygen and equalizes the composition of exhaust gases, which indicates its high efficiency and the absence of fault code P0420.